2005
DOI: 10.1080/13576280500042606
|View full text |Cite
|
Sign up to set email alerts
|

Influence of an Interprofessional HIV/AIDS Education Program on Role Perception, Attitudes and Teamwork Skills of Undergraduate Health Sciences Students

Abstract: A problem-based learning approach combined with standardized patients was effective in enhancing HIV/AIDS interprofessional role perception, enhancing attitudes towards collaboration and interprofessional approaches to HIV/AIDS care and fostering confidence in teamwork skills among pre-licensure health sciences students.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
3
2

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(41 citation statements)
references
References 18 publications
1
35
3
2
Order By: Relevance
“…They also had the highest scores in all three pairs of collaborations after attending the two programs. The posttest findings from the current study are not congruent with previous studies (e.g., Curran, Mugford, Law, & Macdonald, 2005;Hawk et al, 2002;Hojat et al, 2001;Leipzig et al, 2002;Park et al, 2013) that indicated that-among students in medicine, nursing, and social work-the medical students demonstrated the least positive attitude toward interprofessional collaboration. In particular, internal medicine and family practice residents consistently rated collaboration lower than did advance practice nursing and master-level social work students (Leipzig et al, 2002).…”
Section: Discussioncontrasting
confidence: 77%
“…They also had the highest scores in all three pairs of collaborations after attending the two programs. The posttest findings from the current study are not congruent with previous studies (e.g., Curran, Mugford, Law, & Macdonald, 2005;Hawk et al, 2002;Hojat et al, 2001;Leipzig et al, 2002;Park et al, 2013) that indicated that-among students in medicine, nursing, and social work-the medical students demonstrated the least positive attitude toward interprofessional collaboration. In particular, internal medicine and family practice residents consistently rated collaboration lower than did advance practice nursing and master-level social work students (Leipzig et al, 2002).…”
Section: Discussioncontrasting
confidence: 77%
“…This lack of clarity have sometimes been perceived as detrimental to patient care and management of symptoms (Sasahara et al, 2003). Although shared teaching/learning have often been proposed as a means of overcoming barriers between professionals (Filkins, 1999;Curran et al, 2005) it is interesting to note only 1 respondent in the present study reported shared teaching/learning with other professionals.…”
Section: Engagement In Cancer Carecontrasting
confidence: 45%
“…Twelve (16 %) tools measured participants' teamwork skills. Teamwork skills such as leadership, communication and crisis management were assessed through simulation; 41,138,209 however, other tools involved direct observation of skills in actual practice settings, such as medical residents' abilities to lead ward teams 213 and palliative care physicians' communication in team meetings. 195 Behaviors of students, residents/fellows, or practicing physicians were reported outcomes for ten (14 %) tools.…”
Section: Description and Validity Evidence For Teamwork Assessment Toolsmentioning
confidence: 99%